Checklist of the fresh and brackish water snails (Mollusca, Gastropoda) of Bénin and adjacent West African ecoregions - (:unkn) unknown (My University, 2020)
Currently no comprehensive checklist of fresh and brackish water gastropods from Bénin exists, and those for adjacent West African areas are outdated. Yet, such checklists provide essential biodiversity information and a consistent taxonomic and nomenclatural framework for that biodiversity. Here a first checklist of the fresh and brackish water gastropods from Bénin and adjacent West African ecoregions is presented, based on an extensive literature review and field surveys between September 2014 and June 2019 in six major fresh and brackish water ecosystems in Bénin. This inventory includes information on synonymy, species distribution in West Africa, habitats, and conservation status. The fresh and brackish water gas-tropod fauna includes 60 species, belonging to 28 genera and 16 families. Pachychilidae, Ampullariidae, Neritidae, and Bulinidae were the most diverse families with 9, 8, 7, and 7 species, respectively. However, literature and field data indicated that 23 species observed in West African basins that extend to Bénin * Contributed equally as the first authors.
Keywords: African Research